Synthesis of Graphene Oxide from Waste Carbon Tyre using Modified Hummer’s Method - N. Bonnia, N.; Z. Zanuri, A.; A. Asli, N.; A. Masdar, N.; Ratim, S.; M. Yahaya, S.; M. Mahat, M.; Ramli, R. (International Journal of Engineering and Technology, 2019)
Recently, graphene was produced from graphite powder using chemical vapour deposition (CVD) or Hummerâ€™s method. Graphene is widely used in many applications and give a lot of advantages for industry. In this study, graphene oxide was synthesized from waste carbon tyre using modified Hummerâ€™s method. This green technology turned waste material to wealth. The morphology and structural properties of the graphene oxide were investigated using Raman spectroscopy, scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX). Raman analysis was confirmed that graphene oxide was successfully synthesized from waste carbon tyre. It was confirmed the peaks shows that D band and G band was at 1361 cm-1 and 1596 cm-1 with the intensity ratio of the D band relative to the G band (ID/IG) is 0.88. The formation of few sheets of grapheme oxide that stalked together on the surface of the sample structure, bumping pieces and coarse surface was confirmed by scanning electron microscopy (SEM). The elemental composition of carbon (C) is 50.90 % and oxygen (O) is 49.10% which showed a good composition for graphene oxide. All the results were confirmed that the graphene oxide has been synthesized from waste carbon tyre using modified Hummerâ€™s method which next will forms graphene powder through exfoliation method.Â Â